If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(x+3)=8(x+6)
We simplify the equation to the form, which is simple to understand
5(x+3)=8(x+6)
Reorder the terms in parentheses
+(+5x+15)=8*(x+6)
Remove unnecessary parentheses
+5x+15=+8+*(+x+6+)
Reorder the terms in parentheses
+5x+15=+(+8x+48)
Remove unnecessary parentheses
+5x+15=+8x+48
We move all terms containing x to the left and all other terms to the right.
+5x-8x=+48-15
We simplify left and right side of the equation.
-3x=+33
We divide both sides of the equation by -3 to get x.
x=-11
| 14x+12=4x^2 | | 4(r+6)=-49 | | -8x+48=-2(x-2)(x-2)+32 | | X+-1=0 | | -3(r+7)=-40 | | X+-2=0 | | 10(v+2)-2v=2(4v+3)-9 | | 2.87x+25.83=51.66 | | 5r^2=48+r | | -4(r+3)=-61 | | -10x+4=-7x+13 | | 9y-7=28 | | 6(x-2)=(x-4)-28 | | .3x+5=x+3 | | 18x-30= | | .3x+.5=1-0.05x | | f(X)=x^2+6x+1 | | (2x+10)+(6x-4)= | | -7-3y=14 | | 10+25b= | | 8w-6.4=-6.4+5w | | x^2-26x+138=0 | | 1.98g-14=0.89 | | 3(6c-2)=4(10c-7) | | 5x-1=-2 | | 5y-7=-4 | | x^2-x^4=60 | | (.5x+5)-1=-.3(3x-4) | | 3(3u+2v)-3(4u-3v)= | | 4x^2+29x+25=0 | | X^2-Y^2+15X-19Y-6=0 | | 4x^2-25x+19=-2x+4 |